Sex Trade Involvement in São Paulo, Brazil and Toronto, Canada: Narratives of Social Exclusion and Fragmented Identities - Kidd, Sean A.; Coimbra Liborio, Renata Maria [UNESP] (Sage Publications Inc, 2011)
An extensive international literature has been developed regarding the risk trajectories of sex trade-involved children and youth. This literature has not, however, substantially incorporated the narratives of youths regarding their experiences. In this article, the contemporary literature on child and youth sex trade-involvement is reviewed and the findings of a qualitative analysis of the narratives of 14 youth from São Paulo, Brazil and 58 youth from Toronto, Canada are presented. Substantial similarities were found between the groups of narratives with respect to abusive and unstable home experiences, pathways into the sex trade, social exclusion, and the impacts of the sex trade on physical and mental health. Key areas of divergence included the roles of poverty and drug use in entering the sex trade. The implications of shared experiences of social exclusion and fragmented identity across differing sociocultural contexts for policy and intervention are discussed.
Keywords: sex trade; youth; review; qualitative